An analysis of the perceived responsibility, authority, and delegation of powers of district supervisors, principals, and head teachers in the division of Cotabato I - Viloria, Fragedio C. 1929- (s.n.], 1967)
This is an analysis of the perceived responsibility, authority, and delegation of powers of district supervisors, principals, and head teachers in the Division of Cotabato. Presented in a carefully reasoned conception of the nature of leadership responsibilities, the study is helpful in assisting all persons concerned with, and interested in, educational administration and supervision to critically appraise their own views of their jobs.